A homeownership paradox: why do Chinese homeowners rent the housing they live in?. Issue 8 (22nd October 2021) - Huang, Youqin; Yi, Daichun; Clark, William A. V.
Abstract: China is an ownership society, but with a paradox – many homeowners do not live in the apartments/houses they own, and instead live in rental housing. This is different from the pattern in Western economies where households own multiple properties but still live in an owned unit. The paper is situated within the literature on the financialization of housing and the changing meaning of homeownership. We examine the paradox by studying its patterns and dynamics using 2017 China Household Finance Survey data. We find that the owner-renting in China is a result of spatial, temporal and functional mismatches between housing needs. The intrinsic investment strategy and services linked to homeownership have made it imperative to own homes, regardless a household's housing needs. Young, single, better-off and split households, and those in large, expensive cities are more likely to be owners-renting. In addition, institutional barriers in the housing market such as migrant status, housing purchase limit policy, and subsidized housing encourage owner-renting.